2014
DOI: 10.1002/smll.201400842
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Microbeads with a Thermo‐Responsive Shell and a pH‐Responsive Core as a Dual‐Switch‐Controlled Release System

Abstract: Treating inflammation with a dual-switch-controlled release system: The release of a drug from the developed microbead system occurs only in response to both an increase in local temperature and an acidic environmental pH. This dual-switch-controlled release system has the advantages of distinguishing between inflamed and healthy tissues to improve treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…This PVO was molecularly modified to release vanillin in acidic pH and presence of H 2 O 2 to treat ROS-related inflammatory diseases [134]. Vancomycin is used as an inflammatory therapeutic drug which is responsive to dual stimuli of temperature and pH [135]. Inflammatory Bowel Disease (IBD) is a chronic inflammatory disease which can affect the entire GI tract.…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…This PVO was molecularly modified to release vanillin in acidic pH and presence of H 2 O 2 to treat ROS-related inflammatory diseases [134]. Vancomycin is used as an inflammatory therapeutic drug which is responsive to dual stimuli of temperature and pH [135]. Inflammatory Bowel Disease (IBD) is a chronic inflammatory disease which can affect the entire GI tract.…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…Vancomycin was loaded in the nanoparticles as the inflammatory therapeutic drug. This dual stimuli-responsive drug MBs could release the drug only in the presence of both stimuli (temperature and pH), preventing unexpected drug release due to accidental stimulus [ 239 ].…”
Section: Applications Of Stimulus-responsive Systemsmentioning
confidence: 99%
“…Our earlier studies demonstrated the development of inflammation-responsive drug carriers with anti-inflammatory applications. The goal of this work is to develop a CD44/FR-β targeting and catalase (CAT)-loaded photodynamic selenium nanoparticles (SeNPs) for highly selective fluorescence imaging and photodynamic treatment of proinflammatory-activated macrophages. The photodynamic SeNPs can convert endogenous H 2 O 2 that is produced in activated macrophages to oxygen to produce an oxygenated microenvironment.…”
Section: Introductionmentioning
confidence: 99%